2018
DOI: 10.4103/jnsbm.jnsbm_46_17
|View full text |Cite
|
Sign up to set email alerts
|

Tea polyphenols and prevention of epigenetic aberrations in cancer

Abstract: Tea polyphenols are secondary metabolites of tea plants and are well known for beneficial health effects. They can protect from a variety of illnesses including cancers. Tea polyphenols can prevent cancer by modulating epigenetic aberrations taking place in DNA methylation, histone modifications, and micro-RNAs. By altering these epimutations, they regulate chromatin dynamics and expression of genes those induce or suppress cancer formation. However, majority of the studies in existing literature are carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 22 publications
0
26
0
2
Order By: Relevance
“…Therefore, many in vivo studies determine the effect of the amount of consuming green tea on the reduction of incidence of malignant tumors, including colorectal cancer, stomach cancer, liver cancer [19] or lung cancer [38]. These results concern drinking more than ten cups of green tea infusions per day [40]. However, on the other side, one study indicates an increased risk of developing bladder cancer when consuming five to nine cups of green tea infusions per day.…”
Section: Anticancer Potential Of Green Tea Catechins Based On In Vitrmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many in vivo studies determine the effect of the amount of consuming green tea on the reduction of incidence of malignant tumors, including colorectal cancer, stomach cancer, liver cancer [19] or lung cancer [38]. These results concern drinking more than ten cups of green tea infusions per day [40]. However, on the other side, one study indicates an increased risk of developing bladder cancer when consuming five to nine cups of green tea infusions per day.…”
Section: Anticancer Potential Of Green Tea Catechins Based On In Vitrmentioning
confidence: 99%
“…Available literature data indicate that polyphenols derived from green tea exert their antitumor activity due to modification of histones, micro-RNA as well as DNA methylation [40]. Figure 3 presents a summary of molecular signaling pathways of green tea catechin.…”
Section: Anticancer Potential Of Green Tea Catechins Based On In Vitrmentioning
confidence: 99%
“…Nevertheless, high percentage of cell mortality was observed after irradiation and 24‐h incubation (Figure URE 8), especially for Pt NPs synthesized by green chemistry methods. Green tea has been reported to prevent carcinogenesis . It has also been reported that catechins from green tea have a synergetic effect with anticancer drugs in tertiary cancer prevention .…”
Section: Resultsmentioning
confidence: 79%
“…In the literature, anticancer properties of green tea have been reported, which are attributed to the presence of polyphenols, such as epicatechin, epigallocatechin, epicatechin‐3‐gallate, and epigallocatechin‐3‐gallate . Several studies have shown that drinking green tea can prevent carcinogenesis and the development of various types of cancers Moreover, green tea polyphenols are responsible for the regulation of different cancer‐related processes and factors, including DNA methylation and microRNA, histone, and protein modification . Recently, it was shown that green tea plays a very important role in cancer prevention .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation